Apperception as a Communication Event to Foster Mindful Learning in Indonesian Language Learning - Naila Shofa, Anindha; Subyantoro, Subyantoro (International Journal of Language Teaching and Education, 2026)
Apperception is commonly viewed as an introductory learning activity that connects students’ prior knowledge with new material. However, existing research still tends to treat apperception merely as a procedural step and has not sufficiently examined its role as a communicative event that fosters mindful learning. This study aims to describe apperception as a communicative event that promotes mindful learning in Indonesian language instruction. This study employed a qualitative approach using Dell Hymes’s ethnography of communication. It was conducted in Class VIII E at SMPN 2 Kalinyamatan, involving an Indonesian language teacher and students. Data were collected through non-participant observation, semi-structured interviews, documentation, and field notes, and analyzed using the interactive model of Miles, Huberman, and Saldaña, interpreted through Hymes’ SPEAKING components. The findings show that apperception functions as a communicative event constructed through the interrelationships of Setting and Scene, Participants, Ends, Act Sequence, Key, Instrumentalities, Norms, and Genre. These interactions encourage students to activate prior knowledge, relate experiences to learning material, engage in reflective thinking, and develop readiness to learn—key aspects of mindful learning. The novelty of this study lies in integrating apperception, communication ethnography, and mindful learning into a unified framework, demonstrating that mindful learning can emerge through pedagogical communication without requiring specific mindfulness interventions. These findings suggest that apperception should be designed as a dialogic, contextual, and reflective communication process to support more meaningful Indonesian language learning.